Indonesian Consumer Complaint Behavior Based on Ethnic Groups and Generations - Simanjuntak, Megawati; Shahirah, Ilfia (Gadjah Mada International Journal of Business, 2024)
Complaint behavior is a response to consumer dissatisfaction after using goods or services. This study aimed to examine the effect of ethnicity and people’s generations on consumer complaint behavior in Indonesia. The variables used were complaint behavior, ethnicity, and generations. The study collected and analyzed 2,100 items of data using descriptive analysis, one-way ANOVA, and multiple linear regression. The findings showed that consumers in Indonesia rarely complain when disappointed with sellers. Generation Y and the Buginese complained more often than other consumer groups. Furthermore, the results showed significant differences in complaint behavior, based on ethnicity and generation. This study also revealed that complaint behavior was significantly influenced by ethnicity and the baby boomer generation.